Antioxidant cuttlefish collagen hydrolysate against ethyl carbamate-induced oxidative damage. Issue 4 (11th January 2021) - Du, Bowei; Deng, Guiya; Zaman, Fakhar; Ma, Hui; Li, Xuejuan; Chen, Jialiang; Li, Tianyu; Huang, Yaqin
Abstract : Collagen hydrolysate against EC-induced oxidative damage. Abstract : Ethyl carbamate (EC) has been associated with the generation of reactive oxygen species (ROS) and depletion of glutathione (GSH), leading to a decline in cell viability. In this study, we found that the cuttlefish collagen hydrolysate (CCH) exhibited high antioxidant activity in scavenging hydroxyl radicals (IC50 = 0.697 mg mL −1 ), which was also effective in combating EC-induced oxidative damage in liver hepatocellular carcinoma HepG2 cells. The expression of genes related to oxidative stress response could be regulated by CCH to mitigate EC-induced oxidative stress. Pathway analysis confirmed that the protective ability of CCH could be related to ferroptosis and glutathione metabolism. Therefore, CCH could reduce the decline in cell viability by alleviating GSH depletion, and prevent EC-induced oxidative damage. Moreover, protective effect of CCH could be realized by upregulating the heme oxygenase-1 to achieve the preventation of cell sensitization. Considering these effects, CCH has potential for use in food to prevent oxidative stress.